2015
DOI: 10.1080/13504622.2015.1018142
|View full text |Cite
|
Sign up to set email alerts
|

Reducing students’ carbon footprints using personal carbon footprint management system based on environmental behavioural theory and persuasive technology

Abstract: This study applied environmental behavioural theories to develop a personal carbon footprint management system and used persuasive technology to implement it. The system serves as an educational system to improve the determinants of students' low-carbon behaviours, to promote low-carbon concepts and to facilitate their carbon management. To assess the validity of the system, high school students were chosen to participate in an experiment, the results of which reveal (1) the system has significant and positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, this study may have suffered from a self-selection bias where participants have already adopted most of the lifestyle adjustments prior to the study. Another study compared the use of a carbon calculator to a personal carbon footprint management system and found that the footprint management led to a significant reduction in emissions over time, but there was no control condition in the study and the convenience sample of 66 undergraduate students were not randomly assigned to the two conditions (30). Other experiments tested carbon calculators by giving participants bogus, randomly assigned feedback, showing that "worse than peers" or "negative" feedback produced greater pro-environmental intentions driven by social comparisons and mediated by eco-guilt (31)(32)(33)(34).…”
Section: Previous Research On Carbon Calculatorsmentioning
confidence: 99%
“…However, this study may have suffered from a self-selection bias where participants have already adopted most of the lifestyle adjustments prior to the study. Another study compared the use of a carbon calculator to a personal carbon footprint management system and found that the footprint management led to a significant reduction in emissions over time, but there was no control condition in the study and the convenience sample of 66 undergraduate students were not randomly assigned to the two conditions (30). Other experiments tested carbon calculators by giving participants bogus, randomly assigned feedback, showing that "worse than peers" or "negative" feedback produced greater pro-environmental intentions driven by social comparisons and mediated by eco-guilt (31)(32)(33)(34).…”
Section: Previous Research On Carbon Calculatorsmentioning
confidence: 99%
“…It aims to provide students with an embodied experience of change, helping them gain a systemic understanding of how transformations can occur. While similar 30-day change experiments have been carried out in both educational and non-educational settings, the focus is more typically limited to behavioral changes aimed at reducing environmental impacts or carbon footprints (Lin 2016). Such behavioral approaches emphasize the practical sphere of transformation, with less attention to the political and personal spheres.…”
Section: Linking Transformation Theory With Active Learningmentioning
confidence: 99%
“…Similarly, participants in an ecological footprinting study reported that two months after seeing their results, they had made changes in their consumption patterns [28]. Students who completed a carbon footprint calculator in combination with focus group discussions also reported to have made some small changes to their lifestyle as a result [18], and students who used a carbon footprint management system (including various persuasive techniques) on a weekly basis showed reduced carbon emissions after four and six weeks [29]. Finally, a long-term study where a bi-monthly carbon calculator was used as part of a local climate initiative found that the initiative had reduced participants' CO2 emissions [19].…”
Section: Effects Of Ecological Footprint Calculators On Behaviourmentioning
confidence: 99%